Considerations for the use of Cre recombinase for conditional gene deletion in the mouse lens. - Lam, Phuong T.; Padula, Stephanie L.; Hoang, Thanh V. (Tufts University. Tisch Library., 2019)
Background: Despite a number of different transgenes that can mediate DNA deletion in the developing lens, each has unique features that can make a given transgenic line more or less appropriate for particular studies. The purpose of this work encompasses both a review of transgenes that lead to the expression of Cre recombinase in the lens and a comparative analysis of currently available transgenic lines with a particular emphasis on the Le-Cre and P0-3.9GFPCre lines that can mediate DNA deletion in the lens placode. Although both of these transgenes are driven by elements of the Pax6 P0 promoter, the Le-Cre transgene consistently leads to ocular abnormalities in homozygous state and can lead to ocular defects on some genetic backgrounds when hemizygous.; Keywords: Cre recombinase, Lens development, Transgenic mice.; Springer Open.